Lacticaseibacillus paracasei AO356 ameliorates obesity by regulating adipogenesis and thermogenesis in C57BL/6J male mice. (February 2023) - Kim, Young In; Lee, Eun-Sook; Song, Eun-Ji; Shin, Dong-Uk; Eom, Ji-Eun; Shin, Hee Soon; Kim, Jung Eun; Oh, Ju Yeoun; Nam, Young-Do; Lee, So-Young
Graphical abstract: Highlights: Lacticaseibacillus paracasei AO356 decreased high-fat diet-induced body weight gain, and fat mass. Lacticaseibacillus paracasei AO356 decrease adipocyte size and increase skeletal muscle fiber size in C57BL/6J male mice. Lacticaseibacillus paracasei AO356 downregulated the expression of adipogenesis transcription factors in epididymal and subcutaneous fat pads. Lacticaseibacillus paracasei AO356 upregulated the expression of thermogenesis-related genes in epididymal and subcutaneous fat pads. Abstract: Obesity is a metabolic disease caused by the excessive fat accumulation and is a global health problem that affects more than one-third of the population. Probiotics are considered an effective alternate treatment for preventing obesity as FDA-approved anti-obesity drugs are associated with side effects, such as depression, diarrhea, and dyspepsia. Oral administration of Lacticaseibacillus paracasei AO356 (AO356) isolated from healthy female Koreans to high-fat diet-fed C57BL/6J male mice effectively ameliorated body weight gain, abnormal body composition, and obesity-induced hyperleptinemia and inflammation. This effect may be associated with the downregulation of adipogenesis transcription factor-and lipid metabolism related genes, such as Srebp1c, Pparγ, Fas, C/ebpα, and Fabp4 and upregulation of thermogenesis-related genes, such as Ucp1, Cpt1, Pgc1α, Cidea, and Prdm16 in epididymal and subcutaneous fat pads. In conclusion, our results show that AO356 prevents high-fat diet-induced obesity by regulating adipogenesis and thermogenesis.